2023
DOI: 10.1002/cbf.3788
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Rosa damascena extract: Antibacterial activity and its role of adhesion to human epithelial cells in vitro

Abstract: The current study aimed to investigate the inhibitory activity of aqueous extracts of different plant parts of Rosa damascena, represented by the whole rose, petals, and calyces, against clinical isolates of Staphylococcus spp., Escherichia coli, and Klebsiella pneumoniae, and the inhibition of the bacterial cell. The isolates were obtained from the advanced microbiology laboratory for postgraduate studies in the Department of Biology, Faculty of Education for Girls. They were isolated from urinary tract infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Performing a bibliometric overview on the study of R. damascene extracts against pathogenic bacteria, we notice that S. aureus is the most studied bacterium, against which it is confirmed that various types of extracts, including aqueous, ethanolic, and methanolic extracts, show strong antimicrobial activity [ 102 , 103 ]. This is the reason that we also incorporated in S. aureus our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing a bibliometric overview on the study of R. damascene extracts against pathogenic bacteria, we notice that S. aureus is the most studied bacterium, against which it is confirmed that various types of extracts, including aqueous, ethanolic, and methanolic extracts, show strong antimicrobial activity [ 102 , 103 ]. This is the reason that we also incorporated in S. aureus our study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the presence of unknown substances in the extracts poses a challenge in understanding potential synergistic or antagonistic effects among the compounds. Thus, we emphasize the need for caution in interpreting the overall impact of the extracts due to these uncertainties [ 102 ]. Additionally, the strain-specific responses observed in the study’s time-kill curves highlight the complexity of microbial interactions, indicating that certain strains may exhibit higher resistance or require longer exposure times [ 114 ].…”
Section: Limitations Of the Studymentioning
confidence: 99%